Adsorption characteristics of multiple microcystins and cylindrospermopsin on sediment: Implications for toxin monitoring and drinking water treatment. (1st September 2015) - Maghsoudi, Ehsan; Prévost, Michèle; Vo Duy, Sung; Sauvé, Sébastien; Dorner, Sarah
Abstract: Adsorption of mixtures of cyanotoxins onto sediment as a dominant mechanism in the elimination of cyanotoxins from the aqueous phase has not been extensively investigated. The aim of this study was to investigate adsorption and desorption behavior of six microcystins including microcystin (MC)-LR, RR, YR, LY, LW and LF and cylindrospermopsin (CYN) on natural sediment. Freundlich and Langmuir isotherms could be fitted for MC-LR, RR, YR and CYN. Sorption kinetics showed immediate rapid adsorption for all cyanotoxins: CYN, MCLW and MCLF were adsorbed 72.6%, 56.7% and 55.3% respectively within 2 h. Results of desorption experiments demonstrated that less than 9% of cyanotoxins desorbed from sediment within 96 h. Adsorption of cyanotoxins onto three fractionated sediments particles, clay–silt (<75 μm), find sand (75–315 μm) and coarse sand (315–2000 μm) demonstrated that adsorption capacity of coarse sand fraction for all the tested cyanotoxins was less than 4% of the clay–silt fraction. Results of this study revealed that there is a potential for cyanotoxins to accumulate in the sediments of lakes, as well as in drinking water treatment plants. Monitoring programs must consider cyanotoxins in the particulate phase to avoid largely underestimating toxin concentrations following their release from blooms. Highlights: Rapid adsorption of cyanotoxins may occur after a bloom of cyanobacteria and subsequent release of toxins into the environment. CYN, MCRR, MCLF and MCLW showed a high adsorption potential (36.4%–72.6%) for sandy sediments. Cyanotoxins follows a different sorption pattern depending on the variable amino acids in their structure. The adsorption capacity of the coarse sand fraction of the sediment was less than 4% of the clay–silt fraction. There is a potential for cyanotoxins to accumulate in the sediments of lakes and in drinking water treatment plants.